The Northernmost record of the goose genus Chloephaga (Eyton, 1838) (Aves, Anatidae) and its biogeographical implications. (November 2022) - Álvarez-Herrera, Gerardo P.; Agnolín, Federico L.; Méndez, Cecilia; Luna, Carlos; Cuaranta, Pedro; Contreras, Silvina; Zurita, Alfredo E.
Abstract: The aim of the present contribution is to describe a partial coracoid (CTES-PZ 7797) coming from Upper Pleistocene Toropí/Yupoí Formation, in Corrientes province, Argentina. The comparative anatomical analysis indicates that it belongs to an indeterminate species of the goose genus Chloephaga, but sharing some characters with the living C. picta . Today, members of this genus breed in Southern Patagonia and migrate to southern Buenos Aires province during the winter season, being its northernmost record 700 km far south from the fossil specimen here reported. The presence of Chloephaga farther north from its current geographical distribution is congruent with the presence in Upper Pleistocene outcrops in the area of mammals that are adapted to arid environments. This constitutes another taxon recorded at Arroyo Toropí that currently presents a different geographic distribution, such as observed in Leopardus pardalis, Chaetophractus villosus, Boa constrictor, Dolichotis patagonica, among other, and shed light on the complex palaeobiogeographic scenario that could have developed during the MIS 5 in the Mesopotamian region of Argentina. Highlights: A novel record of Chloephaga for the Upper Pleistocene of Mesopotamia is described. A comparative anatomical analysis with living species of Chloephaga is performed. Implications of presence of Chloephaga during MIS 5 in the Mesopotamian region of Argentina are analyzed.